2017
DOI: 10.1158/1078-0432.ccr-16-2128
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cytolytic Activity Stratifies Molecular Subsets of Human Pancreatic Cancer

Abstract: Immunotherapy has the potential to improve the dismal prognosis in pancreatic ductal adenocarcinoma (PDA), but clinical trials, including those with single-agent PD-1 or PD-L1 inhibition, have been disappointing. Our aim was to examine the immune landscape of PDA as it relates to aspects of tumor biology, including neoepitope burden. We used publicly available expression data from 134 primary resection PDA samples from The Cancer Genome Atlas to stratify patients according to a cytolytic T-cell activity expres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
203
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(222 citation statements)
references
References 57 publications
16
203
1
2
Order By: Relevance
“…As reported very recently, PD-L1 expression in PC is not associated to an inflammatory tumor type as defined by an immunogenic gene signature. 39 This could explain the correlation of high sPD-L1 levels with a strong CD3C T cell infiltrate in the absence of a correlation between tumoral PD-L1 expression with sPD-L1 levels.…”
Section: Discussionmentioning
confidence: 99%
“…As reported very recently, PD-L1 expression in PC is not associated to an inflammatory tumor type as defined by an immunogenic gene signature. 39 This could explain the correlation of high sPD-L1 levels with a strong CD3C T cell infiltrate in the absence of a correlation between tumoral PD-L1 expression with sPD-L1 levels.…”
Section: Discussionmentioning
confidence: 99%
“…The fewer mutations could result in a less immunogenic tumor that does not stimulate as robust an immune response from effector T cells as has been suggested for multiple other tumor types (50). However, recent analysis of data from The Cancer Genome Atlas revealed that high T-cell cytolytic activity is not linked with increased mutational burden in PDAC (51). Further analysis is needed to better understand the reasons behind the low CD8-to-CD4 ratio in PDAC, although our proposed use of a 4-1BB mAb would address this issue for in vitro expansion.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of TCGA data indicates that the lack of spontaneous immune infiltration in non-inflamed human melanoma tumors is unlikely due to lack of antigens per se (58). In patients with pancreas cancer, we have reported that the cytolytic index, defined by expression of granzyme A and perforin 1, is inversely proportional to the number of predicted neo-epitopes (59). In tumors with a high degrees of T cell exclusion, blocking only PD-1 or CTLA-4 may be insufficient to achieve a clinical response if other suppressive pathways such as IDO, CD73, TIGIT, VISTA and many others are also expressed and function in a non-redundant fashion regardless of PD-1 or CTLA-4 blockade.…”
Section: What Are We Missing?mentioning
confidence: 99%
“…This approach can be built upon – and merged with – existing infrastructure established over the past years for next generation sequencing and mutation panel test of patient tumors. For example, tumor and normal whole exome sequencing and tumor RNA sequencing can establish a patient’s HLA type, mutational and neo-epitope burden, the tumor genome, and transcriptome from which the composition of the cellular infiltration as well as the constellation of primary suppressive pathways can be bioinformatically determined (59). If successful, based on the immune profile, patients could be matched to effective therapies (and similarly, guided away from costly or toxic ineffective therapies).…”
Section: What Are We Missing?mentioning
confidence: 99%